2007
DOI: 10.1017/s0373463307004456
|View full text |Cite
|
Sign up to set email alerts
|

The First Escort Tractor Voith Tug with a Bulbous Bow: Analysis and Consequences

Abstract: On February, 15th 2005, Gondán S.A. shipyard in the north-west of Spain handed over the escort tractor Voith tug “VELOX” to the Norwegian shipowner Østensjø Rederi AS, the first of this type in the world to incorporate a bulbous bow. After generally making a reference to the benefits obtained by the incorporation of a bulbous bow regarding the reduction of the ship's resistance, we specifically analyse the consequences derived from the incorporation of this appendage in an escort tractor Voith tug concerning i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…On the other hand, taking into consideration the tendency of curves at higher speeds, especially with a rudder angle of 25 • , it could be concluded that at present, there are no escort tugs available in the market with that BP required. Nevertheless, this circumstance is solved in real life using two tugs working in tandem [39], so the BP of each escort tug is added as it is regulated in Los Angeles/Long Beach port [40,41].…”
Section: Models Analysismentioning
confidence: 99%
“…On the other hand, taking into consideration the tendency of curves at higher speeds, especially with a rudder angle of 25 • , it could be concluded that at present, there are no escort tugs available in the market with that BP required. Nevertheless, this circumstance is solved in real life using two tugs working in tandem [39], so the BP of each escort tug is added as it is regulated in Los Angeles/Long Beach port [40,41].…”
Section: Models Analysismentioning
confidence: 99%
“…The consequences of this manoeuvre are presented by Baniela and Diaz (2008): Relatively high-speed navigation is required.Braking or braking and steering is controlled by the tug to maintain a reference angle corresponding to the water flow direction, as opposed to the direction taken by the vessel on tow.…”
Section: Operating Tugs For Escort Assistancementioning
confidence: 99%
“…Figure 14 shows the balance of lateral forces acting on the escort tractor Voith tug involved in indirect operations. It is known that (Baniela and Diaz, 2008; Van der Laan, 2002) three forces act on tugs involved in indirect operations. The balance between them will be represented in an equation for the tug's movement under these conditions: The resultant hydrodynamic forces for lift and drag of the skeg and hull, applied to the Centre of Lateral Pressure (COP) above the quick work of the tug: H f The resultant thrust related to the two cycloidal propellers, whose point of application varies according to the thrust of each propeller: PtThe tug force related to the towline action applied in the staple: T f
Figure 14.Balance of forces acting on the escort tractor Voith tug during the escort manoeuvre.
…”
Section: Controlling Towing Manoeuvres By Operating the Towing Winchmentioning
confidence: 99%
See 1 more Smart Citation